2013
DOI: 10.1186/1752-1947-7-227
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Sheehan’s syndrome presenting with rhabdomyolysis and hyponatremia: a case report

Abstract: IntroductionHyponatremia associated with rhabdomyolysis is a rare event and a correct diagnostic approach is required to rule out this or other diseases as a primary cause and to avoid other complications resulting from a lack of appropriate treatment.Case presentationA 64-year-old Caucasian woman presented to our facility with worsening fatigue, slurred speech, nausea and vomiting, and high serum levels of creatine kinase and myoglobin together with hyponatremia. Normal arterial blood gas analysis results, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…[31][32][33][34] The electromyogram is also important for assessing whether the injury is a myogenic injury, and the electromyogram results of patients that were observed in our study conformed to the changes in RM. [35] It has been reported that the occurrence of RM in patients with Sheehan's syndrome was associated with severe hyponatremia, [10,19] which is also supported by our regression analysis results. Hyponatremia is the most common form of electrolyte disorder in Sheehan's syndrome, in which the pathogenesis is mainly caused by severe hypothyroidism and glucocorticoid deficiency and involves improper secretion of antidiuretic hormone and hypovolemia.…”
Section: Discussionsupporting
confidence: 90%
“…[31][32][33][34] The electromyogram is also important for assessing whether the injury is a myogenic injury, and the electromyogram results of patients that were observed in our study conformed to the changes in RM. [35] It has been reported that the occurrence of RM in patients with Sheehan's syndrome was associated with severe hyponatremia, [10,19] which is also supported by our regression analysis results. Hyponatremia is the most common form of electrolyte disorder in Sheehan's syndrome, in which the pathogenesis is mainly caused by severe hypothyroidism and glucocorticoid deficiency and involves improper secretion of antidiuretic hormone and hypovolemia.…”
Section: Discussionsupporting
confidence: 90%
“…Rhabdomyolysis can occur as a result of electrolyte abnormalities (hypokalemia, hypophosphatemia, hyponatremia, and hypernatremia) in the setting of endocrine diseases such as diabetes 6063 , thyroid dysfunction 64, 65 , primary hyperaldosteronism 66 , primary adrenal insufficiency 67 , central diabetes insipidus 68 , postpartum hypernatremia 69 , and pituitary dysfunction 70 . Cases of rhabdomyolysis have also been attributed to electrolyte disturbances (primarily hypokalemia and hyponatremia) in the setting of laxative and diuretic misuse/abuse 71–73 .…”
Section: Acquired Causes Of Rhabdomyolysismentioning
confidence: 99%
“…We found one such case in the literature in which the patient initially presented with rhabdomyolysis (table 3). 29 She was found to be deficient in all of the anterior pituitary hormones and gave a history from many years ago of having had postpartum haemorrhage plus an inability to lactate following birth 29. There is another report of a late diagnosis of Sheehan syndrome causing acute renal failure but with only a mildly elevated CK (table 3).…”
Section: Discussionmentioning
confidence: 99%